Pengaruh Kepemilikan Manajerial Dan Return On Asset Terhadap Dividend Payout Ratio Pada Perusahaan Sub Sektor Perdagangan Besar Yang Terdaftar Di Bursa Efek Indonesia Periode 2011-2018 - Yusril; Rini Majidah (LPPM STIE Bisnis Internasional Indonesia, 2022)
The study aimed at obtaining empirical evidence on the effect of Managerial. Ownership and Return On Asset on Dividend Payout Ratio. This study was a quantitative study which obtained data from the financial statements of the companies registered at Indonesia Stock Exchange. The sampling technique applied in this study was purposive sampling technique. The sample used in this study were 10 large trading sub-sector companies (manufactured goods & consumer goods) listed on the Indonesia Stock Exchange (IDX) in the period 2011-2018, so that the total sample of 80 companies. The technique of data analysis applied was multiplelinear regression technique. The results of the analysis showed that: (1) the variable Managerial Ownership did not affect Dividend Payout Ratio, (2) the variable Return On Asset affect Dividend Payout Ration, and (3) the variables Managerial Ownership and Return On Asset simultaneously affected Dividend Payout Ratio